Biofortification of staple food crops: Six questions - Nestel, Penelope; Bouis, Howarth E.; Pfeiffer, Wolfgang; Meenakshi, Jonnalagadda V. (International Food Policy Research Institute, 2006)
More than half the world’s population suffers from micronutrient malnutrition. Biofortification of staple food crops is a new public health approach to control vitamin A, iron, and zinc deficiencies in poor countries. Biofortification is the development of micronutrient ‐ dense staple crops using traditional breeding practices and modern biotechnology. It has multiple advantages: it capitalizes on the regular daily intake of a consistent and large amount of the food staples that predominate in the diets of the poor, recurrent costs are low (germplasm can be shared internationally), it is sustainable, and it can reach undernourished populations in remote are as.